Future time perspective and satisfaction with life across Iife span - Martínez, Patricia (2004)
The present  research studies Satisfaction  with  Life and Future Time Perspective, in itsdifferent dimensions (goals, temporal location of goals and temporal altitudes), from adolescence to elder ages. This study evaluated 570 males and females between 16 and 65 years old, from two different socioeconomic levels in Lima, Peru, through a non experimental, evolutionary transversal design. Tools used in this research were the Motivational Induction Method (MIM) and the Temporal Altitudes Scale (TAS) by Nultin (1985), and the Satisfaction with Life Scale (SWLS) by Pavot & Diener (1993). Results show that there are significan! differences on the construction and temporal Iocation of goals, altitudes towards present, past and future and in the levels of Life Satisfaction due to the variable age. lt was also found that socioeconomic leve! influences these processes more than gender.